NILAI TUKAR PETANI JAGUNG BERDASARKAN LUAS LAHAN DI KELURAHAN KAWANGKOAN BAWAH KABUPATEN MINAHASA SELATAN (Corn Farmers Exchange Rate Based on Land Area in Kawangkoan District South Minahasa Regency) - Enjel Abelia Mailangkay; Theodora M. Katiandagho; Eyverson Ruauw (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
This study aimed to determine the exchange rate of corn farmers based on land area in Kawangkoan Bawah Village, South Minahasa Regency. This research was conducted from March to May 2021. The data collected in this study were primary data and secondary data. Primary data were obtained from direct interviews with corn farmers using a questionnaire. Secondary data were obtained from the Kawangkoan Bawah Sub-District Office, the Central Bureau of Statistics, and journal articles relevant to this research. Sampling of 30 respondents was carried out using the purposive sampling method. The data were calculated using the farmer's exchange rate formula with an income concept approach. The results of this study indicated that the exchange rate of farmers with a land area less than 1 Ha was 83.56. This means that farmers with a land area â‰¤Â 1 Ha if they did not have other income sources, the income obtained from corn farming could not meet their daily needs. Meanwhile, the exchange rate of farmers with a land area more than 1 ha was 147.56. This means that farmers with a land area more than 1 Ha could meet their daily needs from corn farming.